Using Pesticides Safely in and around the Southern Home - P.G. Koehler (EDIS)
This document provides guidelines for the safe use of pesticides in and around homes in the southern United States. It covers various pesticide formulations, including liquids, gases, dusts, granules, and toxic baits, and their application methods. The document emphasizes the importance of following label instructions, protecting people and pets from exposure, and preventing environmental contamination. It also discusses the symptoms of pesticide poisoning, safety precautions for applicators, and special considerations for vulnerable populations such as infants, children, the elderly, and individuals with medical conditions.